Development of a methodology for the formation and adjustment of the catalog of defense forces capabilities - Surkov, Oleh (Eastern-European Journal of Enterprise Technologies, 2021)
The study results have made it possible to devise a methodology for the formation and adjustment of the Defense Forces Capabilities Catalog using cluster analysis and the developed tree-like system of basic indicators characterizing groups and subgroups (clusters). That enables stakeholders to form and adjust the Defense Force Capabilities Catalog with the proper quality, according to the uniform developed algorithm and defined identifiers (features). The methodology is intended for use by members of the Inter-Departmental Working Group on Defense Review, as well as working groups in the course of a separate review or capacity assessment. The Defense Force Capabilities Catalog was deconstructed into five levels of hierarchy, each of which contains interdependent typical tasks, organizational structures, and means (systems, complexes). The procedure is to analyze and clearly cluster individual capabilities of the defense forces according to certain features (requirements, characteristics) to group them and include them in the relevant groups, subgroups, and functional capabilities groups. A system of the indicators for the formation and adjustment of the Defense Forces Capabilities Catalog has been proposed, as well as a conformity criterion based on the generalized indicator, which defines the level of formation (adjustment) of the Defense Forces Capabilities Catalog. Seven steps of the procedure have been defined: from identifying individual capabilities based on their description (step 1) to verifying the acceptability of the results obtained (step 7) using the evaluation criterion and specially designed tables. The methodology was tested during a passive experiment in 2020 on the analysis of the current Defense Forces Capabilities Catalog, which made it possible to identify a series of significant shortcomings in its structure and content.